2010
DOI: 10.1016/j.pbb.2010.01.009
|View full text |Cite
|
Sign up to set email alerts
|

The interactive effects of methylphenidate and ethanol on ethanol consumption and locomotor activity in mice

Abstract: The concomitant use of alcohol (EtOH) and the psychotherapeutic agent dl-methylphenidate (MPH) has risen as a consequence of an increase in ADHD diagnoses within the drinking age population. It was recently found that the combination of MPH and EtOH increases the self-report of pleasurable feelings relative to MPH alone. This finding raises concerns regarding the combined abuse liability for these two widely used drugs. The present behavioral study reports on the development of an adult male C57BL/6J (B6) mous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(47 citation statements)
references
References 56 publications
5
42
0
Order By: Relevance
“…In animal models we have previously reported that (1) a sub-stimulatory dose of dl-MPH potentiates a stimulatory dose of ethanol, 14 (2) a depressive dose of ethanol strongly potentiates a stimulatory dose of dl-MPH 15 and (3) combining dl-MPH with ethanol potentiates ataxia. 16 Integrating these preclinical investigations with the present human behavioral time course studies using pure d-MPH-ethanol support an underlying neuropharmacological component to this drug combination synergism.…”
Section: Discussionmentioning
confidence: 99%
“…In animal models we have previously reported that (1) a sub-stimulatory dose of dl-MPH potentiates a stimulatory dose of ethanol, 14 (2) a depressive dose of ethanol strongly potentiates a stimulatory dose of dl-MPH 15 and (3) combining dl-MPH with ethanol potentiates ataxia. 16 Integrating these preclinical investigations with the present human behavioral time course studies using pure d-MPH-ethanol support an underlying neuropharmacological component to this drug combination synergism.…”
Section: Discussionmentioning
confidence: 99%
“…3 mg/kg or less) in behavioral pharmacology experiments is driven by clinical significance. Relatively low doses of MPH are used therapeutically in humans to treat ADHD (Kuczenski and Segal, 2005) and can significantly interact with ethanol in humans (Patrick et al , 2007) and in rodent models (Griffin et al , 2010, 2012a). Further, evidence indicates that low doses of MPH not only affect behavior but also increase extracellular levels of dopamine and norepinephrine in rodents in a regionally specific manner (Balcioglu et al , 2009; Berridge et al , 2006; Koda et al , 2010; Kuczenski and Segal, 1997, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Locomotor activity was assessed using a Digiscan Animal Activity Monitor system, model RXYZCM(8) TAO (Accuscan Instruments, Columbus, OH) that has been described in several publications (Griffin et al , 2012a; Griffin and Middaugh, 2006; Griffin et al , 2012b; Griffin et al , 2010)…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations